Prolegomena : questions to be settled before the study of an author, or a text - Mansfeld, Jaap. (Philosophia Antiqua, 1994)
Prolegomena deals with the introductory and hermeneutic sections of a wide range of commentaries and studies on philosophical, scientific, biblical and other ancient authors. Special attention is given to unclearness as a stimulus for interpretation. New light is shed on the Life of an author (e.g. Plotinus') as a preliminary to the study of his works, and on the part played by the idea that life and doctrine should agree with each other. The results obtained by the study of the practices as well as the avowed principles of ancient scholars and commentators among other things further the understanding of the interrelated philosophical, literary, medical and patristic exegetical traditions, of the book of Diogenes Laërtius, of Galen's autobibliographies and of Thrasyllus' Before the Reading of the Dialogues of Plato .